Erratum: Erratum: KCNQ2 Encephalopathy and Responsiveness to Pyridoxal-5'-Phosphate - Chow, Chit Kwong; Luk, Ho Ming; Wong, Suet Na (Journal of pediatric genetics (Birmingham, Ala.), 2023)
[This corrects the article DOI: 10.1055/s-0040-1721384.].